Effect of Increasing Arginine:Lysine Ratio During Transition and Lactation on Farrowing Kinetics, Milk Composition, and Sow and Litter Performance - Sara Virdis; Abigail K. Jenkins; Jason C. Woodworth; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 90 sows (Line 241, DNA Genetics, Columbus, NE) were used to determine the effect on farrowing kinetics, milk composition, and sow and litter performance of increasing the SID Arginine:Lysine ratio in transition and lactation diets fed to mixed-parity sows. Sows were blocked by parity and body weight (BW) on approximately d 108 of gestation and allotted to 1 of 3 dietary treatments of increasing SID Arg:Lys (90, 105, or 120%). Sows received approximately 6 lb/d of their treatment diet from d 109 of gestation until farrowing after which they were allowed ad libitum access to their treatment diet. Litters were cross fostered within 48 h after farrowing to equalize litter size. SID Arg:Lys did not impact (P > 0.10) sow BW or backfat change during lactation, nor influence sow ADFI either pre farrow or during lactation. Average SID Arg intake increased (linear, P < 0.001) with increasing SID Arg:Lys ratio as expected. Wean to estrus interval decreased then increased (quadratic, P = 0.044) with increasing SID Arg:Lys ratio. No differences were observed (P > 0.10) for the number of total pigs born or for the percentage of total born alive, stillborn and mummified nor did treatment influence the litter size, litter weight, or prewean mortality at any time point. At d10 the average BW of piglets tended to be lower in the 120% SID Arg:Lys ratio treatment compared to the 90% SID Arg:Lys ratio treatment (P = 0.061). Piglet ADG from d 0 to d 10 tended to be greater in the 90% SID Arg:Lys ratio group compared to the 120% SID Arg:Lys ratio group (P = 0.084), while no differences in piglet performance were observed from d 10 to wean or birth to wean. The SID Arg:Lys ratio did not affect (P > 0.10) farrowing duration, colostrum yield, or colostrum intake. Increasing SID Arg:Lys ratio did not affect (P > 0.10) the concentration of IgG in either colostrum and milk and did not impact milk composition or BUN measured in the sow or piglet. This data suggests that increasing SID Arg:Lys ratio from 90 to 120% will not impact farrowing kinetics or sow and litter performance.
Keywords: arginine; gestation; lactation; lysine; sow